Characterization of Modified Cellulose (MC)/Poly (vinyl alcohol) Electrospun Nanofibers for Bone Tissue Engineering - Sugandha, Chahal; Jahir Hussain, Fathima Shahitha; M. M., Yusoff (Elsevier Ltd, 2013)

(untitled)
In bone tissue engineering a variety of polymers were used to develop a suitable artificial bioactive scaffold for bone tissue regeneration. In this present study, we were using modified cellulose. Randomly oriented nanofibrous scaffolds of MC and poly (vinyl alcohol) (PVA) were synthesized by electrospinning technique. The blend solutions of MC/PVA with different weight ratio of MC to PVA were prepared using water as solvent to fabricate nanofibers. The morphology, diameter of electrospun nanofibers was studied using SEM. The crystalline and thermal properties of nanofibers were investigated by DSC and chemical characterization by FTIR analysis. These results showed that MC/PVA nanofibrous scaffold provides a beneficial frame for bone tissue engineering.